Preparation of gallium sulfide nanosheets by liquid exfoliation and their application as hydrogen evolution catalysts - Duesberg, Georg; Coleman, Jonathan; Donegan, John; Nicolosi, Valeria; Mc Evoy, Niall; Mc Closkey, David (My University, 2015)
Here we demonstrate the production of large quantities of gallium sulfide (GaS) nanosheets by liquid exfoliation of layered GaS powder. The exfoliation was achieved by sonication of the powder in suitable solvents. The variation of dispersed concentration with solvent was consistent with classical solution thermodynamics and showed successful solvents to be those with Hildebrand solubility parameters close to 21.5 MPa1/2. In this way, nanosheets could be produced at concentrations of up to ~0.2 mg/ml with lateral sizes and thicknesses of 50-1000 nm and 3-80 layers, respectively. The nanosheets appeared to be relatively defect free although oxygen was observed in the vicinity of the edges. Using controlled centrifugation techniques, it was possible to prepare dispersions containing size-selected nanosheets. Spectroscopic measurements showed the optical properties of the dispersions to vary strongly with nanosheet size, allowing the elucidation of spectroscopic metrics for in-situ estimation of nanosheet size and thickness. These techniques allow the production of nanosheets with controlled sizes which will be important for certain applications. To demonstrate this, we prepared films of GaS nanosheets of three different sizes for use as hydrogen evolution electrocatalysts. We found a clear correlation between performance and size showing small nanosheets to be more effective. This is consistent with the catalytically active sites residing on the nanosheet edges.
PUBLISHED
Export Date: 5 August 2015
Keywords: gallium sulfide (GaS) nanosheets; gallium sulfide (GaS) nanosheets